2019
DOI: 10.1039/c9ra02186h
|View full text |Cite
|
Sign up to set email alerts
|

Exploring metabolic biomarkers and regulation pathways of acute pancreatitis using ultra-performance liquid chromatography combined with a mass spectrometry-based metabolomics strategy

Abstract: Acute pancreatitis (AP), as a common kind of pancreas-based inflammatory disease, is accompanied by a serious and abnormal metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Pancreatic disease is closely associated with the down-regulation of valine. Furthermore, the pathway underlying the biosynthesis of valine is involved in the pathogenesis of acute pancreatitis [ 24 ]. In addition, valine is a component of pancreatic juice [ 30 ]; pancreatic insufficiency might be responsible for valine reductions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pancreatic disease is closely associated with the down-regulation of valine. Furthermore, the pathway underlying the biosynthesis of valine is involved in the pathogenesis of acute pancreatitis [ 24 ]. In addition, valine is a component of pancreatic juice [ 30 ]; pancreatic insufficiency might be responsible for valine reductions.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, metabolomics has been used to identify the etiology of acute pancreatitis [ 22 ] and judge the severity of this disease [ 23 ]. In addition, metabolomics has become a potential tool to differentiate acute pancreatitis from chronic pancreatitis, and pancreatic cancer, as well as other diseases of the digestive system [ 24 28 ]. For example, Huang et al distinguished three types of acute pancreatitis (biliary acute pancreatitis, hyperlipidemia acute pancreatitis, alcoholic acute pancreatitis) by gas chromatography-mass spectrometry-based metabolomics [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2017 ; Guo et al. 2019 ). Succinate, an intermediate in the Krebs cycle, can stabilize hypoxia-inducible factor-1 and stimulate dendritic cells to mediate inflammation (Mills and O'Neill 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of progressive chronic Pt in swine ( Sun et al, 2014 ) and rat ( Tian et al, 2015 ) models showed gradual decreases in PC, GPC, betaine and glycine in the swine model, and changes in aspartate, betaine and lipids, which in the rat model correlated with the degree of fibrosis and/or inflammatory cell infiltration. GC-MS profiling of tissue extracts and serum ( Sakai et al, 2012 ) in mice with acute induced Pt showed significant changes in tricarboxylic acid (TCA) cycle intermediates, glutamate and O- phosphoethanolamine, whereas serum profiling using Ultra Performance Liquid Chromatography (UPLC)-MS suggested that a 19-metabolite signature could distinguish animals with acute Pt from controls ( Guo et al, 2019 ). Recent studies in human subjects have also reported potential blood markers that could distinguish chronic pancreatitis from PDA ( Lindahl et al, 2017 ; Mayerle et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%